THE INFLUENCE OF WORKLOAD AND WORK ENVIRONMENT ON TURNOVER INTENTION : (Study on Employees of the Service Department of PT. Pos Indonesia Jombang Branch) - Rahayu, Annisa Dwi; Hidayati, Nurul (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
The purpose of this study was to examine how the workload and work environment impact turnover intentions among employees at the service department of PT. Pos Indonesia Jombang Branch. Data was gathered through a questionnaire distributed to 30 employees.   The research methodology employed was explanatory in nature.   Findings revealed that workload was positively correlated with turnover intentions, whereas the work environment had a negative association with turnover intentions at the PT. Pos Indonesia Jombang Branch. These results imply that PT Pos Indonesia (Jombang Branch) should prioritize workload management and work environment improvements to boost employee retention rates. By addressing these issues, the organization could cultivate a more content and loyal workforce, ultimately reducing turnover and related expenses. Future studies could delve into other factors like job satisfaction, organizational culture, and job stress to deepen understanding of turnover intentions.